Caregivers evaluate independence in individuals with Down syndrome. Issue 5 (4th February 2022) - Santoro, Stephanie L.; Hendrix, James; White, Nicole; Chandan, Priya
Abstract: Independence is both a sense of autonomy and self‐reliance coupled with the skills to complete tasks without assistance. Questionnaire of caregivers of individuals with Down syndrome asked about factors related to independence on six topics: safety, communication, self‐care, daily living, social/leisure, and vocational/employment. Responses from 408 caregivers to an independence questionnaire were received, and summarized using means and frequencies. Top goals by topic were safety from sexual abuse, communicating wants and needs, toileting independently, living independently/semi‐independently, engaging in leisure time appropriately, and reading and writing. Independence is a complex, multifactorial phenomenon which varies among individuals with DS.